2011
DOI: 10.1093/pcp/pcr078
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of High-CO2-Inducible Extracellular Proteins in the Unicellular Green Alga, Chlamydomonas reinhardtii

Abstract: The unicellular green alga Chlamydomonas reinhardtii can acclimate to a wide range of CO(2) concentrations through the regulation of a CO(2)-concentrating mechanism (CCM). By proteomic analysis, here we identified the proteins which were specifically accumulated under high-CO(2) conditions in a cell wall-less strain of C. reinhardtii which release their extracellular matrix into the medium. When the CO(2) concentration was elevated from the ambient air level to 3% during culture, the algal growth rate increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 55 publications
0
43
0
1
Order By: Relevance
“…Recently, C. reinhardtii proteome, transcriptome and metabolome have been studied under varying CO 2 concentration. Cumulatively, these studies suggest the involvement of novel transport proteins involved in C i transport and also reveal the effect of induction of CCM on whole genome (Yamano et al 2008, Renberg et al 2010, Baba et al 2011, Fang et al 2012). However, effect of CO 2 on other green alga and cynaobacteria has not been investigated so far.…”
Section: Image Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, C. reinhardtii proteome, transcriptome and metabolome have been studied under varying CO 2 concentration. Cumulatively, these studies suggest the involvement of novel transport proteins involved in C i transport and also reveal the effect of induction of CCM on whole genome (Yamano et al 2008, Renberg et al 2010, Baba et al 2011, Fang et al 2012). However, effect of CO 2 on other green alga and cynaobacteria has not been investigated so far.…”
Section: Image Analysismentioning
confidence: 81%
“…Similarly, Fang et al (2012) observed that varying CO 2 concentrations had an effect on 25% of the transcriptome in C. reinhardtii. Proteomic studies on C. reinhardtii under varying concentrations of CO 2 reveal the role of 22 extracellular proteins which are only expressed under low-CO 2 concentration (Baba et al 2011). Similarly, in a transcriptome study, a series of low-CO 2 inducible proteins have Spirulina platensis: exposed sample…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cell wall proteome analysis of H. pluvialis and its cell wall mutants identified a subset of induced proteins known to be involved in wall reconstruction and defense (53,54). Baba et al (2) observed remarkable changes in the amount and composition of extracellular proteins after transfer of Chlamydomonas reinhardtii cells to 3 % co 2 . An extracellular cysteine protease inhibitor was purified from culture filtrate of Chlorella sp.…”
Section: Differentially Secreted Proteins Of Antarctic and Mesophilicmentioning
confidence: 99%
“…Briefly, non-boiled protein samples were separated in 12 % acrylamide gels containing 0.1 % gelatin, and after renaturation in 2.5 % triton X-100 solution at room temperature for 30 min, the gel was rinsed with ddh 2 eDtA) before addition of the loading buffer.…”
Section: Protein Analysismentioning
confidence: 99%